Light Metals 2012 - Suarez, Carlos (The Minerals, Metals & Materials Series,, 2016)
An update of the definitive annual reference source in the field of aluminum production and related light metals technologies, a great mix of materials science and practical, applied technology surrounding aluminum, bauxite, aluminum reduction, rolling, casting, and production.